2016
DOI: 10.1007/s40899-016-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

In situ redox potential measurements as a monitoring technique for hot spring water quality

Abstract: Previous studies on the redox potential of hot springs have indicated that redox potential sensors display a more heightened sensitivity to the HS -/SO 4 2-redox couple, and that redox potential is not related to many different redox couples. However, previous studies have not focused on long-term, continuous measurement of hot spring aquifers. Therefore, three continuous in situ redox potential (Eh) measurements, each lasting approximately 1 month, were conducted using a platinum electrode in a 32°C hot sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…Moreover, this can be implemented long term, continuously, and in situ for large scale applications. Ioka et al (2016) reached the same conclusion in their study when using measured values to monitor hot spring water quality. They used HS − /SO 4 2− and S 2− /SO 4 2− redox couples, because the dominant redox-related species in the hot springs water was sulphur [41].…”
Section: Redox Potential Measurements As a Monitoring Technique For Seo 3 2− Reductionsupporting
confidence: 65%
“…Moreover, this can be implemented long term, continuously, and in situ for large scale applications. Ioka et al (2016) reached the same conclusion in their study when using measured values to monitor hot spring water quality. They used HS − /SO 4 2− and S 2− /SO 4 2− redox couples, because the dominant redox-related species in the hot springs water was sulphur [41].…”
Section: Redox Potential Measurements As a Monitoring Technique For Seo 3 2− Reductionsupporting
confidence: 65%
“…The other factor affecting ORP measurements is the time of result stabilization. Tests conducted by Gómez et al (2006) and Ioka et al (2011Ioka et al ( , 2016 indicate that sometimes the stable values might be observed after at least a week.…”
Section: Essentials Of Oxidation-reduction Potential In Groundwatermentioning
confidence: 96%
“…Third, low-density microplastics can easily move with the monsoon and be deposited on lakeshore sediments near estuaries. Fourth, human activities are intensive in coastal areas, and the spatial variability of microplastics is mainly influenced by the extent, path, and location of human activities [62]; thus, the abundance of microplastics is relatively great in shallow waters near the coast. In ecosystems, biological uptake is a key aspect of the microplastic transport process, and microplastics in sediments are taken up by a large number of aquatic organisms, including fish [63].…”
Section: Ecological Risk Assessment Of Microplasticsmentioning
confidence: 99%